2001
DOI: 10.1177/0145482x0109500402
|View full text |Cite
|
Sign up to set email alerts
|

Adding Audio Description: Does it Make a Difference?

Abstract: A television viewing experiment-preceded and followed by interviews about attitudes, usual television viewing patterns and demographics-was conducted with 111 legally blind adults who were convened in groups. The research examined the impact of watching television science programs with and without audio description. The experiment showed that respondents gained and retained more information from watching programs with description. Respondents reported that description makes programs more enjoyable, interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 3 publications
3
39
0
2
Order By: Relevance
“…While there were positive opinions comments regarding the quality of the conventional version for all clips (similar to results found in studies by [13,14]), particularly for clip 2, no conventional version of any clip had more positive opinion comments than the first person narrative version. This may be due to the fact that people were familiar and satisfied with the conventional type of DVI and did not think it was necessary to contribute positive comments.…”
Section: Video Tape Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…While there were positive opinions comments regarding the quality of the conventional version for all clips (similar to results found in studies by [13,14]), particularly for clip 2, no conventional version of any clip had more positive opinion comments than the first person narrative version. This may be due to the fact that people were familiar and satisfied with the conventional type of DVI and did not think it was necessary to contribute positive comments.…”
Section: Video Tape Analysissupporting
confidence: 84%
“…There have been relatively few studies [13,14] that have investigated the impact of DVI on people who are blind. Most of these studies compared participant performance on a multiple choice test and attitudes between content containing description and content without it.…”
Section: Introductionmentioning
confidence: 99%
“…He found that the observable degree of regularity of words in the VD corpus might facilitate the automatic production of VD. Peli [25], Pettit [26], Schmeidler [27] and Ely [28] reported on evaluations done by the VII on the value and importance of VD.…”
Section: The Nature Of Vdmentioning
confidence: 99%
“…Pettitt et al 1996;Peli et al 1996;Schmeidler and Kirchner 2001;Luque 2009). From this point of view, the audience's response -both cognitive and emotional -becomes, together with the professionals' ethical choices, the keystones for establishing solid theoretical postulates and efficient working guidelines.…”
Section: Introductionmentioning
confidence: 99%